The euro and corporate financing before the crisis - Bris, Arturo; Koskinen, Yrjö; Nilsson, Mattias (Journal of Financial Economics, 2014)
We study the financing policies of European public corporations prior to the euro crisis. Using data from 11 euro countries and a control group of five other European countries over 1991–2006, we show that nonfinancial firms from euro countries with previously weak currencies considerably increased their debt financing after the introduction of the euro. The results are stronger for large firms, firms dependent on external financing, and for the latter part of the post-euro time period. Overall, the results support the hypothesis that the supply of capital increased following the introduction of the euro.